초등학생의 스마트폰 사용습관과 척추 만곡 및 목·어깨 통증과의 연관성 - 송문구; 박지현; 공지영; 강현식 (Exercise science (Seoul, Korea), 2020)
PURPOSE: This study investigated the relationships of smartphone usage with spinal curvature and neck or shoulder pain in a sample of school children. METHODS: Participants were elementary school children (152 boys, 156 girls). Spinal parameters such as trunk inclination (TI), kyphotic angle (KA), and fleche cervical (FC) were measured with a spine and posture analyzer (DIERS Formetric 4D). In addition, smartphone addiction score (SAS), experience of neck or shoulder pain, postural habits, and lifestyle risk factors were assessed with a standardized questionnaire. Children were classified as good- and poor-posture group according to cervical postures while using a smartphone and as low, medium, and high-risk group according to the SAS levels. Logistic regression was used to determine the odds ratio (OR) and 95% confidence interval (95% CI) of pain experience. RESULTS: With respect to postures, children with poor posture had significantly higher values of TI, FC, and pain experience than children with good posture children. Children with poor posture had a significantly higher risk of neck or shoulder pain (OR=6.51, 95% CI=3.63-11.67, p<.001) compared with children with good posture (OR=1). With respect to the severity of smartphone addiction, there were significant incremental trends in KA, FC, and pain experience according to the SAS-based subgroups (from low to high-risk group). The medium- and high-risk groups had significantly higher risks of neck or shoulder pain (OR=4.77, 95% CI=1.93-11.78, p<.001 and OR=16.51, 95% CI=6.40-42.54, respectively) compared with the low-risk group (OR=1). CONCLUSIONS: The current findings suggest that smartphone addiction and poor posture are two modifiable risk factors in determining the severity of spinal curvature and risk of neck and shoulder pain in school children. KCI Citation Count: 0